Islamic Communication Ethics in Study Films on Protagonists in the Film Iqro My Universe - M. Zanur Syaputra; Ahmad Zulfikar Ali (Values: Jurnal Kajian Islam Multidisiplin, 2025)
Representationis a form of words, images, sequences, stories, etc. that represent ideas, feelings, facts, etc. These representations depend on existing signs and images, which are understood culturally. In the Big Indonesian Dictionary (KBBI), representation can be defined as the act of representing or the state of representation is called representation. This research examines specifically Islamic communication ethics in the film Iqro My Universe. The aim of this research is to find out the Islamic communication ethics contained in the film as well as the representation of Islamic communication ethics. This research uses Roland Barthes' semiotic analysis theory. The research method used in this research is a qualitative descriptive method, with a media text analysis approach. The research subject is the film Iqro My universe which is 101 minutes long and there are 8 scenes analyzed. The data collection technique used is by watching films repeatedly to find and confirm the signs that will be revealed in the film, collecting the data found, and looking for supporting sources of information such as books, journals, documents and internet media. It was concluded that the research findings in this film, researchers found 8 scenes of Islamic communication ethics in the film Iqro My Universe. The film Iqro My Universe is a sequel film which is a film that offers something new that has not existed before in Indonesia, namely combining three concepts: family, religion and science. which contains Islamic communication ethics such asGood words, correct words, words that are effective, simple and easy to understand, noble words, gentle and affectionate.